Meteorological drought under historical and future climate scenarios in North Gojjam sub-basin, Abay River basin of Ethiopia. - Tatek Belay; Tadele Melese; Baye Terefe; Simachew Bantigegn Wassie; Teshager Zerihun Nigussie (PLoS ONE, 2025)
The impacts of climate change are expected to vary considerably across regional and local scales, underscoring the urgent need for localized assessments. This study investigates the spatio-temporal characteristics of meteorological drought across three distinct periods- baseline (1985-2018), near future (2020-2050), and mid-future (2051-2081) under two climate scenarios: SSP2-4.5 and SSP5-8.5, within the North Gojjam sub-basin of the Abay Basin, Ethiopia. It further examines long-term trends in precipitation and both minimum and maximum temperatures across the sub-basin. Future climate projections were derived using six global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) under the Shared Socioeconomic Pathways (SSPs). Data from seven stations were extracted, bias-corrected, and aggregated using R software and relevant analytical packages. Key statistical metrics confirm a strong alignment between corrected GCM outputs and observed historical data. Meteorological drought was assessed using the Standardized Precipitation Evapotranspiration Index (SPEI) over a three-month scale, with run theory applied for drought characterization. Precipitation and SPEI trends were analyzed using the Mann-Kendall test and Sen's slope estimator, with statistical significance set at p < 0.05. Projections suggest an increase in both minimum and maximum mean annual temperatures during the near and mid-future periods, with minimum temperatures rising more sharply. Under SSP5-8.5, precipitation is expected to decrease, except during the mid-future period. The SPEI indicates an intensification and increased frequency of severe drought events. The northeastern and southeastern parts of the North Gojjam sub-basin are particularly vulnerable, posing significant risks for agriculture and water resource management. This study provides critical localized insights into future climate scenarios, highlighting the importance of temporal drought forecasting and the need for targeted adaptation and mitigation strategies in the region.